Analisa Kerusakan Bantalan Bola (Ball Bearing) Berdasarkan Signal Getaran - Muhamad Riva’i; Nanda Pranandita (Politeknik Manufaktur Negeri Bangka Belitung, 2018)
Measurement of the damage of elements in bearing can be by measuring the vibration generated in the form of a frequency signal when the pad is rotating. Measurement of vibration on the bearing by using vibration measuring instrument. Damage to the rolling bearing includes damage to the cage, outer ring, inner ring and balls. The rolling bearings used in this study are deep groove ball bearing type 6003 RS with internal diameter (d) = 17 mm, outer diameter (D) = 35 mm, bearing thickness (B) = 10, number of rolling elements (Nb) = 10 pieces, and the diameter of the rolling element (Bd) = 4.75 mm. In the rotation of the bearing (Fr) = 2003 rpm (33.38 Hz) we found the experimental results of bearings that have been damaged in the outer race at 138 Hz frequency, inner race damage at 196 Hz frequency, (ball) at a frequency of 88.8 Hz and cage damage at a frequency of 13.8 Hz